Faktor-Faktor Penyebab Putus Sekolah KB Injeksi 3 Bulan - Machfudloh; Emi Sutrisminah (Jurnal Health Sains, 2022)
3-month injection KB is a contraceptive that is given every 3 months. Each birth control injection contains the hormones progestin and medroxyprogesterone. The importance of the 3-month injection KB for the sake of creating the welfare of mothers and children. Most of the mothers in Indonesia choose the 3-month injection KB and it is one of the favorite contraceptives because it is easy to do. However, on average, many mothers from 3 months of KB injections drop out. Drop out of family planning participants nationally reached 27%. There are several factors that can cause family planning participants to drop out, these include failure, complications, changing methods, side effects, costs and accessibility, divorced acceptors or husband dies, husband does not agree, frequency of infrequent sexual intercourse, wants to get pregnant or wants to get pregnant. having children soon and menopause. Objective To examine more deeply about the knowledge of the factors that cause dropout for 3-month injections in Indonesia. The method in this study is a scoping review. Search literature in this study using 2 databases, namely Pubmed, Ebsco and 1 search engine, namely Google Scholar published in the last 5 years (2016 – 2021), free access. The total search results were 27 articles, and 10 articles were found that met the inclusion criteria, namely the 3-month injection KB dropout factor. Results: Based on the results of the review that has been explained through the article above, it shows that there are factors that can cause the incidence of dropping out of 3-month injections, including the husband's support factor, the knowledge factor, the affordability factor for health services, and the side effect factor.